2011
DOI: 10.3892/etm.2011.357
|View full text |Cite
|
Sign up to set email alerts
|

Kuromoji (Lindera umbellata) essential oil-induced apoptosis and differentiation in human leukemia HL-60 cells

Abstract: Abstract. Essential oils diluted from certain plants have been shown to have antitumor activity against several human tumor cell lines. Kuromoji (Lindera umbellata) essential oil (KEO) has long been used in Japan as a traditional medicine. KEO and its major chemical constituent, linalool, were investigated in this study for their ability to induce apoptosis and differentiation in human leukemia HL-60 cells. HL-60 cells were treated with 5 or 50 µg/ml KEO or linalool for 24 or 48 h. Then, cell proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Linalool is a terpenoid that is commonly present in plants, such as citrus [ 7 ]. It is known that linalool possesses several bioactivities, such as antibacterial [ 8 ], antiviral [ 9 ], antifungal [ 10 ], anti-inflammatory, and anticancer properties [ 11 , 12 ]. Additionally, it is a perfumery compound that is used in air fresheners [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Linalool is a terpenoid that is commonly present in plants, such as citrus [ 7 ]. It is known that linalool possesses several bioactivities, such as antibacterial [ 8 ], antiviral [ 9 ], antifungal [ 10 ], anti-inflammatory, and anticancer properties [ 11 , 12 ]. Additionally, it is a perfumery compound that is used in air fresheners [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of KEO constituents was conducted by gas chromatography-MS at the Aomori Prefectural Industrial Technology Research Center, as described in an earlier report. 17) The GC-MS system (GC-17A/QP-5000; Shimadzu, Kyoto, Japan) was equipped with a DB-1701 column (30 mm  0:25 mm  0:25 mm; J&W Scientific). The carrier gas was helium.…”
Section: Methodsmentioning
confidence: 99%
“…Tel/Fax: +81-172-39-3790; E-mail: hayatosp@cc.hirosaki-u.ac.jp Abbreviations: LPS, lipopolysaccharide; NO, nitric oxide; IL-6, interleukin-6; TNF-, tumor necrosis factor-; NO, inducible NO synthase; COX-2, cyclooxygenase-2; NF-B, nuclear factor-B; PPAR , peroxisome proliferator-activated receptor containing linalool showed antitumor activity against several human tumor cell lines. 17) In addition, Peana et al have reported that linalool and the corresponding ester (linalyl acetate) exhibited anti-inflammatory activity in rat inflammation model experiments. 18) Therefore, KEO containing linalool and other terpenoids is necessary to elucidate anti-inflammatory principles.…”
mentioning
confidence: 99%
“…bungeana [201] trans-Sabinene hydrate (64) Z. clinopodioides subsp. rigida (0.1%) [21] Antiviral (HSV-1) [282] Moderate repellent (against tick Amblyomma americanum) [305] Z. tenuior [94] Anti-inflammatory (in carrageenan-induced edema and inhibition of hyperalgesia induced by L-glutamate and prostaglandin E2 in rats) [311]; anti-inflammatory (through inhibition of the expression of TNF-α and IL-6 in LPS-stimulated RAW 264.7 cells) [312]; antiinflammatory (in cigarette smoke-induced ALI in mice through inhibiting NF-κB activation) [313] Cytotoxic (human amelanotic melanoma cell line C32, renal cell adenocarcinoma ACHN, hormone-dependent prostate carcinoma LNCaP) [314]; induction of apoptosis (variety of human leukaemia cells) [315][316][317] Hypocholesterolemic (through inhibition of HMG-CoA reductase and conversion of lanosterol to cholesterol) [318,319] Protective effect against t-BOOH induced mutagenesis [194] Review on some effects on cardiovascular system [221] Sedative and anxiolytic [320]; antidepressant [321]; GABAA receptor modulation [322] OH Z. clinopodioides subsp. rigida [21] Z. tenuior [94] p-Menth-3-en-8-ol (65)…”
Section: Ohmentioning
confidence: 99%
“…rigida [21] Z. clinopodioides subsp. rigida (12.5%) [21] Z. tenuior (53.97%) [179] Linalool ( Anti-inflammatory (in carrageenan-induced edema and inhibition of hyperalgesia induced by L-glutamate and prostaglandin E 2 in rats) [311]; anti-inflammatory (through inhibition of the expression of TNF-α and IL-6 in LPS-stimulated RAW 264.7 cells) [312]; anti-inflammatory (in cigarette smoke-induced ALI in mice through inhibiting NF-κB activation) [313] Cytotoxic (human amelanotic melanoma cell line C32, renal cell adenocarcinoma ACHN, hormone-dependent prostate carcinoma LNCaP) [314]; induction of apoptosis (variety of human leukaemia cells) [315][316][317] Hypocholesterolemic (through inhibition of HMG-CoA reductase and conversion of lanosterol to cholesterol) [318,319] Protective effect against t-BOOH induced mutagenesis [194] Review on some effects on cardiovascular system [221] Sedative and anxiolytic [320]; antidepressant [321]; GABA A receptor modulation [322] Analgesic activity reviewed [199] Review on metabolism and toxicity [200] Molecules 2016, 21, 826 20 of 53 [296]; antioxidant [273,[297][298][299] Review on some effects on cardiovascular system [221] Gastroprotective effects in the acute and chronic ulcer models in rats [300] Positive allosteric modulator of the GABAA receptors in primary cultures of mouse cortical neurons [301] Anti-hyperglycemic and anti-hyperlipidemic activity in high fat-induced type 2 diabetic C57BL/6J mice [302] and protective effect in nephropathy [303] Analgesic activity reviewed [199] Review on metabolism and toxicity [200]; general review on thyme and 62 [304] cis-Sabinene hydrate …”
Section: Ohmentioning
confidence: 99%